Distribusi Penyakit Bulai Jagung (Peronosclerospora maydis) pada Lahan Pertanaman Jagung dengan Pendekatan Geostatistik - Hery Nirwanto; Sutikno Sutikno (Politeknik Negeri Lampung., 2024)
Downy mildew Peronosclerospora spp. is an important disease in corn (Zea mays L.). The damage of downy mildew caused by Peronosclerospora spp. is this pathogen can reach 90-100%, especially in corn varieties that are susceptible to downy mildew. So far, most research has only been limited to knowing the incidence of the disease, without being able to describe the spatial distribution pattern of downy mildew in the planting area. This research aims to determine the occurrence of disease and the spatial distribution patterns of downy mildew on a geospatial basis. Samples were taken from three corn fields affected by downy mildew on three fields planted with corn plants that were attacked by downy mildew. Data on the level of infestation, along with its coordinates, were used to create a theoretical semivariogram model, Gaussian, spherical, exponential. The distribution pattern is approached by interpolating attack level data using the kriging method. The research results show that the appropriate theoretical semivariogram model to describe the distribution of P. maydis in the observation area is the Gaussian model. The distribution of pathogens throughout the observation area began with a clustered pattern and evened out at the end of the observation. Foci had a clustered pattern in the first to fourth weeks of observation. Then each foci experienced development, so that the distribution pattern changed to become even after the fifth week of observation.